The association between ten anthropometric measures and osteoporosis and osteopenia among postmenopausal women - Jingyuan Zhang; Yuqi Wang; Jun Guo; Heng Liu; Zhuolin Lei; Shouquan Cheng; Hong Cao (Scientific Reports)
Abstract Osteoporosis and osteopenia pose substantial public health challenges, particularly among postmenopausal women. Although various anthropometric measures have been proposed for risk assessment, their predictive performance and nonlinear relationships with bone outcomes remain unclear. We analyzed data from six consecutive cycles (2007–2018) of the National Health and Nutrition Examination Survey (NHANES). A total of 4473 postmenopausal women aged ≥ 50 years were included, each classified as having normal bone density, osteopenia, or osteoporosis based on dual-energy X-ray absorptiometry measurements. Ten anthropometric indices—waist-to-height ratio (WTHR), conicity index (CI), a body shape index (ABSI), body roundness index (BRI), lipid accumulation product, visceral adiposity index, cardiometabolic index, atherogenic index of plasma, weight-adjusted-waist index (WWI), and triglyceride–glucose (TyG) index—were examined using multiple logistic regression, restricted cubic spline curves, threshold-effect analyses, and SHAP (SHapley Additive exPlanations) analysis to assess their associations with osteoporosis and osteopenia. In fully adjusted models, individuals with higher WTHR, CI, BRI, WWI, and TyG tended to have a lower likelihood of osteoporosis or osteopenia (p < 0.01), whereas those with elevated ABSI were more likely to be diagnosed with these conditions (p < 0.01). Notably, several indices showed nonlinear effects on bone outcomes. Receiver operating characteristic (ROC) analyses indicated that WTHR and BRI had the highest discriminative capacity for differentiating osteoporosis from osteopenia. SHAP analysis further highlighted WTHR and BRI as the most influential predictors. WTHR and BRI demonstrated strong predictive utility for osteoporosis and osteopenia, suggesting their potential as noninvasive, cost-effective screening metrics for postmenopausal bone health. These findings provide insight into the varying roles of central and general obesity indicators in bone density and underscore the importance of incorporating novel anthropometric indices into early-stage risk assessment.